Sport-related concussion in Brazilian professional soccer: A four-year prospective epidemiological analysis - Guilherme Corrêa de Araújo Moury Fernandes; Ewerton Borges de Souza Lima; Paulo Henrique Schmidt Lara; Ana Camila de Castro Gandolfi; Jorge Roberto Pagura; Gustavo Gonçalves Arliani; Moisés Cohen (Sports Medicine and Health Science)
This study aimed to investigate the incidence and other significant features of craniomaxillofacial trauma (CMFT), particularly Sport-Related Concussion (SRC), among professional soccer players from two major leagues in Brazil. This is a prospective epidemiological study which assessed two divisions of the national championship and large regional one over four seasons. Data were gathered from soccer clubs and their medical staff using two online forms. Data related to players (age and position) and injuries (diagnosis, type, body location, laterality, field location, tests performed, need for surgery, time lost in sports, and recurrence) were collected. Between 2016 and 2019, a total of 15 seasons, comprising 3 828 matches and 126 ​324 hours (h) of gameplay, were analyzed. A total of 299 CMFT cases were reported, with a median incidence of 2.37 per 1 000 ​h of play. Among them, there were 178 head and 121 face traumas, which led to 87 SRC (representing 29.10% of all CMFT), with an incidence of 0.69. Defensive midfielders (14.43%) and goalkeepers (14.00%) had the highest prevalence rates of CMFT. Only 3.68% of the injuries, mostly lacerations and fractures, required surgical treatment. This study identified that the average time lost in sports due to SRC was 5.12 days, with a recurrence rate of 12.71%. SRC are a frequent consequence of CMFT in Brazilian professional soccer. Although most cases are mild, there is a high recurrence rate, which may have long-term implications.